Rheumatic diseases and COVID-19 - Wallace, Zachary (Henry Stewart Talks, 2020)
The risk factors of a SARS-Cov-2 infection, How infection can affect rheumatic disease symptoms, The possible increased risk of rheumatic diseases from a SARS-CoV-2 infection, Current investigation strategies and future directions